Porosity measurement of solid pharmaceutical dosage forms by gamma-ray transmission - de Oliveira, Jose Martins; Andreo Filho, Newton; Chaud, Marco Vinicius; Angiolucci, Tatiana; Aranha, Norberto; Germano Martins, Antonio Cesar [UNESP] (Pergamon-Elsevier B.V. Ltd, 2010)
The aim of the present work is the determination of porosity in tablets by using the gamma-ray transmission technique Tablet dissolution depends on some inherent characteristics of the manufacturing process, such as compression force, tablet volume, density and porosity, nature of excipients, preparation methods and its physical-chemical properties Porosity is a measure of empty spaces in a material and can be determined by various techniques In this paper, we propose the use of a gamma-lay transmission technique to obtain the porosity of experimental formulation of tablets. The results of porosity were compared with those obtained by using conventional methodology (density and mercury intrusion) The experimental setup for gamma-ray transmission consists of a gamma-ray source of (241)Am (photons of 59.6 keV and an activity of 3.7 x 10(9) Bq), an Nal(Tl) scintillation detector, collimators and a standard gamma-ray spectrometry electronics. Our results suggest that the gamma-ray transmission technique is a powerful tool for non-destructive porosity quantification of solid pharmaceutical forms and presents smaller errors than those obtained with conventional methodologies (C) 2010 Elsevier Ltd. All rights reserved
Keywords: Porosity; Density; Gamma-ray transmission; Attenuation; Tablet